Penyuluhan Pengelolaan Sampah di Desa Sungai Lueng - Bahrina, Intan; Etika Sari (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Waste is the useless remains of daily human activities that are thrown into the environment. Waste management is the activity of collecting, transporting, processing and recycling waste which is carried out to reduce the impact of waste on health, the environment or aesthetics, as well as to reduce the amount of waste. The aim is to educate the public about the importance of waste management so that people have the awareness to change their behavior in managing it. rubbish. The method used was lectures and using leaflets to the community. This method explains the concept of waste and waste management. This extension was highly supported and welcomed by the community and village officials. This can be seen from the enthusiasm of the community in listening to the material presented and wanting to hold other activities/programs regarding waste management in Sungai Lueng Village which will certainly benefit the surrounding community.